IMPLEMENTASI DAN PENGEMBANGAN WEBSITE PROFIL SEKOLAH UNTUK MENINGKATKAN KUALITAS INFORMASI DAN TAMPILAN SMP PORIS INDAH - Rohan Nurhadi Putra; Achmad Illiyin; Damar Rahmat; Egi Galih Nurizqi; Rdihoni Meison; Oscar Restu Waruwu; Norita Sinaga (Abdi Jurnal Publikasi, 2026)
This community service activity aims to implement and develop a school profile website as a digital information medium at Poris Indah Middle School. The school profile website plays a crucial role in conveying information about the school's identity, vision and mission, academic activities, and various school activities to the wider community. Prior to this PKM activity, the distribution of school information was limited to the surrounding community and had not been integrated into easily accessible digital media. The implementation method included interviews with school officials to meet needs, system design, website development, and delivery of materials to the school. The website was designed with a simple, informative, and responsive appearance so that it could be accessed through various devices. After the development process was completed, socialization was conducted with the school regarding how to manage and update website content. The results of the activity showed that the developed school profile website was able to present school information in a more structured, clear, and easily accessible manner to students, parents, and the general public. The website also serves as the school's official communication medium for conveying announcements, activities, and achievements. In addition, the more modern website appearance helps improve the school's image in the community.